Avaliação da confiabilidade de pilares curtos em concreto armado projetados segundo a NBR 6118:2003 - Henrique Alves Tartaglia Nogueira (2006)
Several studies have demonstrated the economical feasibility of the utilization of highstrength concrete (HSC) in the lower columns of high- and medium-rise buildings. Several international codes have already updated their recommendations to deal with this relatively new material. In spite of the recent revision of the NBR 6118:2003, the Brazilian code has its range of applicability limited to 50 MPa concrete characteristic strengths. However, higherstrength concretes are being successfully used in Brazil and the nonexistence of design recommendations related to this material represents an impediment to the safe and economicalutilization of HSC. Due to its large application, type of failure, and importance to structural integrity, the safety evaluation of HSC columns is a very important issue. In the case of columns, several design parameters are uncertain (concrete compressive strength, cross-sectional dimensions, loads, etc.). As such, safety can be established in probabilistic terms only. In order to simplify the design process, the prescribed reliability levels are introduced in the design codes, in an implicit manner, through the partial safety factors in the limit states design format. As such, the main objectives of this research are: (i) evaluate the reliability levels implicit in NBR 6118:2003 and NBR 8681:2003 for the design of short columns subjected to axial loads and uniaxial bending; (ii) select target reliability levels; (iii) evaluate the influence of design parameters in the resulting reliability levels; (iv) recommend adjustments in the NBR 6118:2003 provisions in order to extend the range of application of this code up to 80 MPa characteristic strengths. The results obtained have shown that, for 50 MPa characteristic strengths, the NBR 6118:2003 provisions imply in reliability levels smaller than those obtained for 20 to 35 MPa columns. Also, the mere extrapolation of current recommendations for 65 or 80 MPa concretes would result in low reliability levels. Nevertheless, adjustments in the equivalent stress block, while other recommendations remain unchanged, would result in adequate reliability levels for all the concrete strengths investigated.